The MASIV Legacy: Surveying AGN Intra-day Variability at Radio Wavelengths. Issue Volume 9:Issue S304(2013) (25th July 2014) - Koay, J. Y.; Macquart, J.-P.; Rickett, B. J.; Bignall, H. E.; Jauncey, D. L.; Pursimo, T.; Reynolds, C.; Lovell, J. E. J.; Kedziora-Chudczer, L.; Ojha, R.
Abstract: The Micro-arcsecond Scintillation-Induced Variability (MASIV) Survey and its follow-up observations have provided large datasets of AGN intra-day variability (IDV) at radio wavelengths. These data have shown that IDV arises mainly from scintillation caused by scattering in the ionized interstellar medium (ISM) of our Galaxy, based on correlation with Galactic latitudes and line-of-sight Galactic electron column densities. The sensitivity of interstellar scintillation (ISS) towards source angular sizes has provided a new tool for studying the most compact components of radio-loud AGNs at microarcsecond (μas) scale resolution - much higher than any ground-based radio interferometer. We present here key results from the MASIV Survey and its follow-up observations, and point to relevant papers where these results have been published.